2020
DOI: 10.1016/j.sjbs.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal effect of synthetic pyrethroid pesticide on metabolic enzymes and protein profile of non-target Zebra fish, Danio rerio

Abstract: Extensive application of pesticide in agricultural field affects the enzymatic activity of non-target animals, including fishes. In this study, the impact of sublethal concentration of fenvalerate on marker enzymes of freshwater Zebra fish was evaluated. Pesticide-induced stress can specifically affect non target fishes, through elevated level of reactive oxygen species which is responsible for biochemical, cell metabolism and physiological activities. The oxidative stress mediated by fenvalerate at sub lethal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…This reduction of CAT activity was probably due to excess production of ROS or peroxidative damage to the liver tissue. The findings of Firat and Tutus [ 22 ], corroborate to present findings as CAT activity decreased after 96 h of EMB exposure in liver tissue in case of O. niloticus , in the liver of L. rohita exposed with profenofos [ 54 ], and in liver and gill tissue of Danio rerio [ 55 ]. However, Prusty et al [ 50 ] noticed that gill CAT activity remains unaffected due to fenvalerate exposure to L. rohita though the liver SOD activity declined.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This reduction of CAT activity was probably due to excess production of ROS or peroxidative damage to the liver tissue. The findings of Firat and Tutus [ 22 ], corroborate to present findings as CAT activity decreased after 96 h of EMB exposure in liver tissue in case of O. niloticus , in the liver of L. rohita exposed with profenofos [ 54 ], and in liver and gill tissue of Danio rerio [ 55 ]. However, Prusty et al [ 50 ] noticed that gill CAT activity remains unaffected due to fenvalerate exposure to L. rohita though the liver SOD activity declined.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, in the present study, the gill, and muscle showed an elevation in SOD activity which may be because, gill and muscle play a major role in the xenobiotics metabolism and gill functions of defense mechanism, which counteracts the oxidative stress induced by EMB pesticides thus maintain cellular membrane integrity [ 1 ]. It was also observed that fenvalerate exposed zebrafish [ 55 ] and L. rohita [ 50 ] showed a decline in SOD activity in gill tissue as compared to the control. Concentration and time duration-dependent increase in SOD activity due to sub-lethal exposure to ivermectin has been observed in Clarias gariepinus [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides are frequently applied to agricultural commodities to enhance the quality and quantity of food. The unrestricted, heavy use of synthetic chemical pesticides results in deleterious until lethal effects on various non-target organisms in aquatic environments, including fish, and direct or indirect effects to users (Kalavathy et al 2001;Kumaresan et al 2018;Ranjbar Jafarabadi et al 2019;Sathyamoorthi et al 2019;Vignet et al 2019;Al-Ghanim et al 2020). Extensive application of pesticides in the agricultural field implies that fish accumulate various fold higher concentrations of chemical residues than the surrounding water in the aquatic environment because of the bioaccumulation phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated pesticide damage skeletal system, various vital organs of fish and cause biochemical alterations in fish. The pesticide hazard to aquatic organism is further increased by biomagnification of the synthetic pesticides from water by aquatic organisms [15] . The pesticide causing neurotoxicity, biochemical changes, hormonal alteration, reproductive toxicity, developmental abnormalities.…”
Section: Introductionmentioning
confidence: 99%